From Family Business to Family Entrepreneurship: Embracing Innovation and AI in the Evolution of Family Ventures - Tomášková, Andrea; Knihová, Ladislava (Publishing House of Wroclaw University of Economics and Business, 2024)
The transition from ‘family business’ to ‘business family’, or ‘family entrepreneurship,’ is a significant shift towards a conceptually diversified and innovative approach in family businesses. This model emphasises the importance of adapting to market changes and preserving key attributes, namely values and traditions. Collaboration among universities and family businesses brings new insights, innovative solutions and best practices to enhance competitiveness. Preserving values, traditions, and sustainability is crucial to the success of family businesses, at the same time collaboration among universities, businesses and communities brings economic and social development benefits but requires continuous development of educational programmes.
Tomášková, A. & Knihová, L. (2024). From Family Business to Family Entrepreneurship: Embracing Innovation and AI in the Evolution of Family Ventures. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), The Importance of Universities for Society and Economy. The Experience of Researchers from the Visegrád Group (pp. 147-159). Publishing House of Wroclaw University of Economics and Business.
Keywords: innovation; family business; tradition; universities